From survival goals to economic rationality: the determinants of farmer households' dual decision regarding land rental area - Li, Hanning; Feng, Jingwen; Peng, Wenhuan (Frontiers in Sustainable Food Systems, 2023)
Introduction Large-scale land rentals are a fundamental way of realizing the moderate-scale operation and transformation of modern agriculture. As the suppliers and main demanders in the land rental market, the decision-making logic of farmer households determines the scale of land rentals. However, land rentals have been plagued by the prominent issues of farmer households' insufficient participation and fragmented rental transactions. It is importance and urgent to promote farmer households' participation in large-scale land rental market. Methods Based on a sample of 4,815 farmer households from the China Family Panel Studies (CFPS) database, this study applied Bivariate Tobit (Bi-Tobit) model to investigate the correlation between farmer households' decisions of rented-in and rented-out area, and analyzed the determinants and inherent logics of the decision making. Heterogeneity analysis was made to examine the difference in surplus and indebted farmer households. Results The results showed that there was a significantly negative correlation between the household rented-in area and the rented-out area. The land value had significantly positive effect on the rented-in area and the rented-out area. Household social security had a significantly positive effect on the rented-out area, but had no significant effect on the rented-in area. For indebted households, only social security significantly affected their decisions of rented-out area, while for surplus households, land value rather than social security became the significant determinant of rented-in and rented-out area. Discussion Farmer households' land rented-in area and rented-out area have comprised a dual decision with a significant negative correlation. Facing the dual functions of creating economic value and providing social security of rural land, farmer households' decision-making logic of rented-in area is dominated by economic rationality, whereas that of rented-out area involves the coexistence of economic rationality and survival rationality. With the improvement of household income level, the dominant logic of the decisions of land rental area transformed from survival rationality to economic rationality. Policies should enhance the rural social security system to increase land rental area, especially by providing adequate social security for farmer households with a lower income level.